The Influence of Entrepreneurship Education and Entrepreneurial Environment on Entrepreneurial Intentions Through Entrepreneurial Motivation in Private Vocational School Students in Mojokerto Regency - Aryati, Sinda Octin (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The purpose of this study was to determine the influenceof entrepreneurship education and entrepreneurial environment on entrepreneurial intentions through entrepreneurial motivation in private vocational school students in Mojokerto Regency. Design/methodology/approach: The population in this study was 233 students of Private Vocational School in Mojokerto Regency. Data collection using closed questionnaires. Data analysis techniques use descriptive statistics and Structural Equation Modeling Partial Least Squares (SEM-PLS). Research Findings: The results showed that 1. There is a direct influence of entrepreneurship education on entrepreneurial motivation; 2. There is an influence of the entrepreneurial environment on entrepreneurial motivation; 3. There is a direct influence of entrepreneurship education on entrepreneurial intentions; 4. There is a direct influence of the entrepreneurial environment on entrepreneurial intentions; 5. There is a the direct influence of entrepreneurial mot ivation on entrepreneurial intentions; 6. There is an indirect influence of entrepreneurship education on entrepreneurial intentions through entrepreneurial motivation; 7. There is an indirect influence of the entrepreneurial environment on entrepreneurial intentions and entrepreneurial motivation Theoretical Contribution/Originality: Based on the search results, it seems that the question is asking for a contribution to theory and originality regarding the influence of entrepreneurship education and entrepreneurial environment on entrepreneurial intentions through Entrepreneurial Motivation in private vocational school students in Mojokerto Regency.